1.
a) \((a + b + c)^2 + (a - b - c)^2 +( b - c - a) ^2 + (c - a - b)^2 \)
\(= (a + b + c)^2 + (a + b - c)^2 + (a - b - c)^2 + (a - b + c)^2 \)
\(= (a + b)^2 + 2c(a + b) + c^2 + (a + b)^2 - 2c(a + b) + c^2 + (a - b)^2 - 2c(a - b) + c^2 + (a - b)^2 + 2c(a - b) +c^2 \)
\(= 2(a + b)^2 + 2c^2 + 2(a - b)^2 + 2c^2 \)
\(= 2[(a + b)^2 + (a - b)^2] + 4c^2 \)
\(=2(2a^2 + 2b^2) + 4c^2 \)
\(= 4(a^2 + b^2 + c^2)\)
b) Đặt: \(x=a+b; y=c+d; z=a-b; t=c-d \)
Ta được:
\((x+y)^2+(x-y)^2+(z+t)^2+(z-t)^2 \)
\(= (x^2+2xy+y^2)+(x^2-2xy+y^2)+(z^2+2zt+t^2)+(z^2-2zt+t^2) \)
\(= 2x^2+2y^2+2z^2+2t^2 \)
\(= 2(x^2+y^2+z^2+t^2) \)
\(=2.\left[(a+b)^2+(c+d)^2+(a-b)^2+(c-d)^2 \right]\)
\(= 2(a^2+2ab+b^2+c^2+2cd+d^2+a^2-2ab+b^2+c^2-2cd+d^2) \)
\(= 2(2a^2+2b^2+2c^2+2d^2) \)
\(= 4(a^2+b^2+c^2+d^2)\)